Cidade sinfônica: a cidade representada em Berlin: Die Sinfonie der Großstadt - Cavalcanti, Andrei de Ferrer e Arruda (2015)
In the universe of research that make intercession between film and architecture and urbanism, a framework dominated by panoramic approaches is identified. In contrast, the present study aims deepening this relationship by looking at intercessions in a specific movie - Berlin: Die Sinfonie der Großstadt (Walter Ruttmann, Germany, 1927). Representative of the film genre known as 'urban symphonies', the film builds in its narrative a generic day in the late 1920s of Berlin; thus, makes room to try to understand the historical context, the customs of the, then called, Weimar Republic, the centre of a rich architectural and urban culture, embryo of the modern movement, which propagated at the time by the publications by the Bauhaus, the Novembergruppe , and the magazine G: Material Elementaren zur Gestaltung. In this research, it is questioned the film's ability to represent, as well as an episode of the urban history of Berlin for showing the daily life in the city, to also represent an episode of the history of town planning, as it uses cinema’s own tools to allude to a functionality and rationality desired by theorists and planners of the time, represented here by architect Ludwig Hilberseimer’s theory. On the path, this research will deal with the relationship between cinema and the city, in addition to film, architectural and urban culture of the time that is expressed in the film and the avant-garde theories that marked the twentieth century.